Politeţea ca mediere – o posibilă genealogie a modernităţii culturale - Caius Dobrescu (Revista de Istorie și Teorie Literară)
The paper Politeness as Mediation: A Possible Genealogy of Cultural Modernity looks at the European culture of polite manners form the perspective of its capacity of inciting and nurturing the transformations of values and mental frameworks generally termed “modernization”. We start form the diffusionist model of the “civilizing process” notoriously promoted by Norbert Elias, but move on to amending it through a vision of politeness as a dynamic cultural device mediating between civic duty and civility, publicity and intimacy, social hierarchy and social equality. The present exploration sets the premises for the further analysis of two related processes: a) the historical influence of the culture of politeness and of polite conversation in Eastern Europe; b) the strategic role played by literary criticism in the revival of the “civilizing process” (seen as a process of “conversational” modernization) under the East European post-Stalinist regimes.